2022
DOI: 10.3390/ijerph19116808
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Isolation Types on Quality of Life during the Coronavirus Disease 2019 Pandemic in Saudi Arabia: A Cross-Sectional Study

Abstract: COVID-19 has caused a global pandemic that has spread rapidly to six continents, with over 2.5 million deaths from December 2019 to March 2021. The number of confirmed COVID-19 cases is still growing worldwide, and quarantines have been recommended to prevent the disease’s spread. However, quarantines affect people’s quality of life (QOL). The aim of this study is to assess the effect of social isolation—quarantine—on QOL during the first wave of the COVID-19 pandemic in Saudi Arabia. A cross-sectional, descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…It is estimated that COVID-19 self-isolation was a factor in reducing both PCS and MCS. In contrast, among two Saudi studies, one by Aisha Alhofaian et al found a value of 44.7 for PCS of 44.7 and 34.6 for MCS [47], while the study by Manal Mohammed Hawash et al found a value of 41.65 for PCS and 32.34 for MCS [48].…”
Section: Discussionmentioning
confidence: 88%
“…It is estimated that COVID-19 self-isolation was a factor in reducing both PCS and MCS. In contrast, among two Saudi studies, one by Aisha Alhofaian et al found a value of 44.7 for PCS of 44.7 and 34.6 for MCS [47], while the study by Manal Mohammed Hawash et al found a value of 41.65 for PCS and 32.34 for MCS [48].…”
Section: Discussionmentioning
confidence: 88%
“…As individuals age, they often face myriad health challenges that require more than just medical treatment [30]. These challenges can include chronic diseases, mobility issues, mental health conditions, and social isolation, all of which can significantly impact their quality of life (QoL) [31]. Multidisciplinary teams are well equipped to address these diverse needs by integrating medical care with psychological support, rehabilitation services, and social interventions [32].…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, house arrest has been implemented in many countries to prevent the spread of the virus. When these restrictions are considered in general terms, they have caused significant changes in many areas of people's daily lives such as health, economic status and eating habits, physical mobility [3]. The pandemic has caused difficulties in accessing healthcare, especially for those without COVID-19 [4].…”
Section: Introductionmentioning
confidence: 99%